The Influence of Charismatic Leadership, Recruitment and Organizational Culture on the Performance of Islamic Boarding School Employees Nurul Jadid Paiton - Agustin, Lisa; Setyanti, Sri Wahyu Lelly Hana; Farida, Lilik; Titisari, Purnamie (Formosa Journal of Applied Sciences, 2024)
Pondok Pesantren Nurul Jadid is one of the organizations engaged in general education and Islamic education. The aim of the organization is to provide general and Islamic education to students. This study aims to determine and analyze the influence of charismatic leadership, recruitment, and organizational culture on the performance of the employees of the Pondok Pesantren Nurul Jadid Paiton. The data analysis method used is multiple linear regression analysis. The results showed that charismatic leadership, recruitment, and organizational culture had a positive and significant impact on the performance of the employees of the Pondok Pesantrem Nurul Jadid Paiton. Based on the results of the study, it can be concluded that charismatic leadership, recruitment, and organizational culture can affect the performance of the employees of Pondok Pesantren Nurul Jadid Paiton.